Forensic Linguistics and Trademark Infringement (El-Wahat Journal for Research and Studies, 2021)
Trademark infringement, notwithstanding its importance as a motive of action in trademark regulation, has not unfortunately been as sufficiently as should have been in the linguistic area and particularly in forensic linguistics.We try through this paper shed light on the contributions of forensic linguistics in an attempt to identify how do forensic linguists deal with linguistic issues related to the law.We also aim at defining the different methodologies  by which forensic linguists may be of help in such trademarks disputes . Keywords-Infringement .Forensic linguistics.Trademark.Ownership.Product.